Effects of UV‐B and heavy metals on nitrogen and phosphorus metabolism in three cyanobacteria. (17th November 2015) - Yadav, Shivam; Prajapati, Rajesh; Atri, Neelam
Abstract : Cyanobacteria sp. (diazotrophic and planktonic) hold a major position in ecosystem, former one due to their intrinsic capability of N2 ‐fixation and later because of mineralization of organic matter. Unfortunately, their exposure to variety of abiotic stresses is unavoidable. Comparative analysis of interactive effect of UV‐B and heavy metals (Cd/Zn) on nitrogen and phosphorus metabolism of three cyanobacteria ( Anabaena, Microcystis, Nostoc ) revealed additive inhibition ( χ 2 significant p < 0.05) of NH4 + and PO4 3− uptake whereas increase in nitrate uptake upon UV‐B + heavy metal exposure. Glutamine synthetase and Alkaline phosphatase activity was reduced after all treatments whereas Nitrate reductase activity showed slight stimulation in UV‐B and UV‐B + heavy metals treatment. Combination of UV‐B and metals seems more detrimental to the NH4 +, PO4 3− uptake, GS and APA activity. A significant stimulation in NO3 − uptake and NR activity following exposure to UV‐B in all the three cyanobacteria suggests UV‐B‐induced structural change(s) in the enzyme/carriers. Metals seem to compete for the binding sites of the enzymes and carriers; as noticed for Anabaena and Microcystis showing change in Km while no change in the Km value of Nostoc suggests non‐competitive nutrient uptake. Higher accumulation and more adverse effect on Na + and K + efflux proposes Cd as more toxic compared to Zn.